Integrated natural resource management and democratization processes Ajuy, Iloilo, Philippines - Fernandez, Pepito R., Jr. (Iloilo City UP Visayas, 2003)
"This paper examined the major development programs/projects that operate in the varied ecological zones (i.e., coastal, lowland, upland) in the municipality of Ajuy, Iloilo, Philippines. The study site was purposively chosen due to its diverse development or management. Using qualitative research methods, the study examines natural resource development programs/projects and how planned development interventions relate to and alter democratization processes (i.e., increased participation of beneficiaries and presence of decentralized or co-managemetn schemes that promote self-reliance) in the study sites. The paper reveals that international development initiatives play a major role in the planning and implementation of development programs/projects in various ecological zones in Ajuy, Iloilo. The experience of Ajuy illustrates that well-meaning international development initiatives in favor of environmental protection, through decentralization and people's participation, do not necessarily enhance the process of democratization and local development. In fact, initiatives are not promoting equal protection of interests among program/project participants. There is also a looming threat that increased expectations and natural resource conflicts among various actors/institutions may disrupt the promotion of resilient management systems if development initiatives are not decentralized and sustained beyond the program/project cycle."
Keywords: Natural resources -- Iloilo